Sites of violence : gender and conflict zones - Giles, Wenona Mary, 1949-; Hyndman, Jennifer (Berkeley : University of California Press, 2004)
In conflict zones from Iraq and Afghanistan to Guatemala and Somalia, the rules of war are changing dramatically. Distinctions between battlefield and home, soldier and civilian, state security and domestic security are breaking down. In this especially timely book, a powerful group of international authors doing feminist research brings the highly gendered and racialized dimensions of these changes into sharp relief. In essays on nationalism, the political economy of conflict, and the politics of asylum, they investigate what happens when the body, household, nation, state, and economy become sites at which violence is invoked against people. In particular, these hard-hitting essays move us forward in our understanding of violence against women-how it is perpetrated, survived, and resisted. They explore the gendered politics of ethno-nationalism in Sri Lanka, the post-Yugoslav states, and Israel and Palestine. They consider "honor killings" in Iraqi Kurdistan, armed conflict in the Sudan, and geographies of violence in Ghana. This volume augments feminist analysis on conflict zones and contributes to transnational coalition-building and feminist organizing.
Feminist approaches to gender and conflict. Gender and conflict in a global context / Wenona Giles ; Jennifer Hyndman -- The continuum of violence : a gender perspective on war and peace / Cynthia Cockburn -- The sounds of silence : feminist research across time in Guatemala / Cathy Blacklock ; Alison Crosby -- Violence against women in war and postwar times. Like oil and water, with a match : militarized commerce, armed conflict, and human security in Sudan / Audrey Macklin -- No "safe haven" : violence against women in Iraqi Kurdistan / Shahrzad Mojab -- From pillars of Yugoslavism to targets of violence : Interethnic marriages in the former Yugoslavia and thereafter / Mirjana Morokvasic-Müller -- Geographies of violence : women and conflict in Ghana / Valerie Pretson ; Madeleine Wong -- Gender, the nationalist imagination, war, and peace / Nira Yuval-Davis -- Feminist analyses of international organizations and asylum. Refugee camps as conflict zones : the politics of gender / Jennifer Hyndman -- The "purity" of displacement and the reterritorialization of longing : Muslim IDPs in the northwestern Sri Lanka / Malathi de Alvis -- Escaping conflict : Afghan women in transit / Asha Hans -- War, flight, and exile : gendered violence among refugee women from post-Yugoslav states / Maja Korac -- The gendered impact of multilateralism in the post-Yugoslav states : intervention, reconstruction, and globalization / Edith Klein -- Feminist futures : negotiating globalization, security, and human displacement. New directions for feminist research and politics / Wenona Giles and Jennifer Hyndman.
Includes bibliographical references (pages 317-345) and index.
Description based on online resource; title from digital title page (ProQuest Ebook Central, viewed on September 11, 2024).
eBooks on EBSCOhost
Keywords: Violence; Political violence; Social conflict; Women -- Crimes against; Sex role; Sex differences; Feminist theory; Violence; Violence politique; Conflits sociaux; Femmes -- Crimes contre; Rôle selon le sexe; Différences entre sexes; Théorie féministe.; violence; terrorism; sex role; social conflict; SOCIAL SCIENCE -- Violence in Society; SOCIAL SCIENCE -- Gender Studies; Feminist theory; Political violence; Sex differences; Sex role; Social conflict; Violence; Women -- Crimes against; Feminismus; Frau; Gewalt; Politik; Politischer Konflikt; Geweld; Etnische conflicten; Vrouwen; Sekserol; Aufsatzsammlung